2023
DOI: 10.1002/fsn3.3358
|View full text |Cite
|
Sign up to set email alerts
|

Functional exploration of taro starch (Colocasia esculenta) supplemented yogurt

Abstract: Stabilizers are essential components of manufactured products such as yogurt. The addition of stabilizers improves the body, texture, appearance, and mouth feel of yogurt while also preventing technical defects such as syneresis. A study was conducted to optimize the concentration of taro starch in yogurt. The yogurt was fortified at different concentrations of taro starch. Taro starch levels were 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, and 3%, with different storage times (0, 14, and 28 days). The Tukey honesty test wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…In another study, the modified starch improved the properties of yogurt more effectively than natural starch at 0.5% concentration, in terms of yield stress, consistency, apparent viscosity, thixotropy, and pseudoplasticity (Pang et al, 2019). Similar results were observed in a study with native starch of taro (Colocassia esculenta) (Shaheryar et al, 2023).…”
Section: Apparent Viscositysupporting
confidence: 69%
See 1 more Smart Citation
“…In another study, the modified starch improved the properties of yogurt more effectively than natural starch at 0.5% concentration, in terms of yield stress, consistency, apparent viscosity, thixotropy, and pseudoplasticity (Pang et al, 2019). Similar results were observed in a study with native starch of taro (Colocassia esculenta) (Shaheryar et al, 2023).…”
Section: Apparent Viscositysupporting
confidence: 69%
“…and found that both varieties exhibit a higher capacity to absorb and retain water, leading to gels with higher viscosity, reduced syneresis, and the maintenance of an intense white color. Shaheryar et al (2023) successfully used 2% starch from taro to reduce the occurrence of syneresis and upgrade the waterholding capacity, viscosity, texture, and appearance in yogurt, increasing storage days. hood.…”
Section: Introductionmentioning
confidence: 99%
“…The starch extraction method using wet pathways depends on the kind of tuber or root that will be extracted. The process of taro starch extraction [1] is carried out through the cleaning, peeling, and cutting of the taro, followed by filtration of the taro puree through a muslin bag to obtain a starch slurry. The starch slurry is left to rest, so the supernatant settles, before emptying it to produce an accumulated wet starch filtrate.…”
Section: Wet Pathwaymentioning
confidence: 99%
“…Camila de Campoa [12] reported the application of zeaxanthin nano-particles in yogurt, improving the physicochemical properties and carotenoid release of yogurts. Recently, several plant components have been reportedly added to yogurts; for example, the juices from grapes and berries [13], saffron floral extracts [14], perilla seed oil [15], carrao (Cassia grandis L.) [16], dietary fiber from grapefruit [17], and taro starch (Colocasia esculenta) [18]. Researchers evaluated the impacts of these plant components on the physicochemical properties (including pH, acidity, color, sensory scores, and syneresis) and textural parameters (like hardness and viscosity), and found that they were essential for the market acceptance and shelf life of yogurt products.…”
Section: Introductionmentioning
confidence: 99%